Smartphone Addiction and Associated Factors among Secondary School Students in Bangladesh: A Cross-Sectional Study - Shanzida Khatun; Mst. Shohana Khanom Itee (Universitas STRADA Indonesia, 2026)
Background: Smartphone addiction is a serious problem among school students worldwide. For Bangladesh, where about half of the population uses smartphones, it is linked with behaviour challenges and academic outcomes. Purpose: The present study aimed to evaluate to smartphone addiction and associated factors among secondary school students of Bangladesh. A descriptive cross-sectional study was conducted with 186 ninth- and tenth-grade students from Rayerbazar High School in Dhaka, selected via convenience sampling. Methods: The study was conducted after institutional review board approval from NIANER on December 2019 to February 2020 using a self-administered questionnaire on demographic data, usage patterns, and a validated addiction scale. Descriptive statistics, Pearson's correlation, t-tests and ANOVA were performed. The mean addiction score was 3.33 (SD=0.90). Results: The father's educational attainment level (p=0.003), socioeconomic status (p=0.002) and family living status (p=0.021) were noted as significant associations. In addition, there was a significant correlation between higher scores and the use of smartphones (p<0.001), the duration of daily smartphone use (p<0.001), social networking (p<0.001) and gaming (p=0.021). Findings are important because the cross sectional design precludes causal inferences, but it is easy to see implications. Conclusion: School nurses should include regular health screening that incorporates an assessment for addiction in all medical practices. It is recommended that guidelines be created to set limits on recreational screen time for school health. Offline social interaction and student education on digital balance are key strategies in adolescent health promotion.